Metagenomic insights into ultraviolet disinfection effects on antibiotic resistome in biologically treated wastewater. (15th September 2016) - Hu, Qing; Zhang, Xu-Xiang; Jia, Shuyu; Huang, Kailong; Tang, Junying; Shi, Peng; Ye, Lin; Ren, Hongqiang
Abstract: High-throughput sequencing-based metagenomic approaches were used to comprehensively investigate ultraviolet effects on the microbial community structure, and diversity and abundance of antibiotic resistance genes (ARGs) and mobile genetic elements (MGEs) in biologically treated wastewater. After ultraviolet radiation, some dominant genera, like Aeromonas and Halomonas, in the wastewater almost disappeared, while the relative abundance of some minor genera including Pseudomonas and Bacillus increased dozens of times. Metagenomic analysis showed that 159 ARGs within 14 types were detectable in the samples, and the radiation at 500 mJ/cm 2 obviously increased their total relative abundance from 31.68 ppm to 190.78 ppm, which was supported by quantitative real time PCR. As the dominant persistent ARGs, multidrug resistance genes carried by Pseudomonas and bacitracin resistance gene bac A carried by Bacillus mainly contributed to the ARGs abundance increase. Bacterial community shift and MGEs replication induced by the radiation might drive the resistome alteration. The findings may shed new light on the mechanism behind the ultraviolet radiation effects on antibiotic resistance in wastewater. Graphical abstract: Highlights: Application of high-throughput sequencing to characterize bacterial community and antibiotic resistome. Increase of total relative abundance of ARGs in wastewater by ultraviolet radiation. Crucial roles of bac A and RND-related genes in the ARGs abundance increase by ultraviolet radiation. Contribution of bacterial community shift and MGEs replication to the resistome alteration.